The Impact of Marketing Mix on Customer Satisfaction in Haidilao Hotpot - Hee Song Ng; Thiam Yong Kuek; Luo Kuan Zhang; Lee Kean Yeoh; Jing Huan Zhang; Yu Hui Yuan; Harshika Sharma; Harshit (Global Academia Publisher, 2022)
Haidilao Hotpot is a China hotpot catering company and the largest chain of hotpot restaurants in China. This study examines how the customer satisfaction of Haidilao Hotpot in China is influenced by the 4Ps Marketing Mix: Product, Price, Place, and Promotion. A survey questionnaire was used for data collection. A total of 150 customers of Haidilao Hotpot in China participated in the online survey via Wen Juan Xing. SPSS computer program is also adopted to analyse further the data obtained from the respondents. Besides, some research papers are used to strengthen and support the current study. The findings showed that place and promotion were positively correlated to customer satisfaction. Promotion is the most significant variable influencing customer satisfaction in Haidilao Hotpot. However, product and price did not significantly affect customer satisfaction. The implications for policymakers and practitioners, as well as the future direction of research are discussed. This study provides Haidilao Hotpot with valuable insights and guidance to increase customer satisfaction in China.